How to Survive the Anthropocene: Adaptive Atheism and the Evolution of Homo deiparensis - Shults, Fount LeRon (Religions, 2015)
Why is it so easy to ignore the ecological and economic crises of the Anthropocene? This article unveils some of the religious biases whose covert operation facilitates the repression or rejection of warnings about the consequences of extreme climate change and excessive capitalist consumption. The evolved defaults that are most relevant for our purposes here have to do with mental credulity toward religious content (beliefs about supernatural agents) and with social congruity in religious contexts (behaviors shaped by supernatural rituals). Learning how to contest these phylogenetically inherited and culturally fortified biases may be a necessary condition for adapting to and altering our current natural and social environments in ways that will enhance the chances for the survival (and flourishing) of Homo sapiens and other sentient species. I outline a conceptual framework, derived from empirical findings and theoretical developments in the bio-cultural sciences of religion, which can help clarify why and how gods are imaginatively conceived and nurtured by ritually engaged believers. Finally, I discuss the role that adaptive atheism might play in responding to the crises of the Anthropocene.